A comparative study of oral Ketoconazole versus Itraconazole in the treatment of Tinea versicolor (Community Based Medical Journal, 2021)
Tinea (pityriasis) versicolor is a superficial fungal infection and one of the most commonly found pigmentary disorders of the skin caused by the yeast Malassezia. Multiple topical as well as systemic therapies are available for treatment. Systemic therapies are used for extensive disease, frequent relapse or where topical agents have failed. The aim that translates the rationale of the study was to compare the efficacy, safety, tolerability and cost effectiveness of oral ketoconazole dose 200mg daily for 7 days versus a single dose of 400 mg of itraconazole in the treatment of tinea versicolor. A total of 64 patients (aged 18-50 years) were selected for the study from the period of June 2019 to November 2019 in the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Bangladesh. Cases having extensive involvement were diagnosed clinically and confirmed by wood's lamp and KOH microscopy was taken. Patients were randomly allocated into equal groups. Group A was given oral ketoconazole dose 200mg daily for 7 days and Group B has given a single dose of 400 mg of itraconazole. 47 (73.4%) male and 17(26.6%) female were included in the study. The mean age of group A was 29.2(SD±8.6) and in group B 28.2(SD±8.5) years. The mean duration of the disease in group A was 3.9(±2.7) months and 3.5(±2.2) months in group B. In group A clinical responders was found cure 25(78.1%), improvement 5(15.6%) and failure in 2(6.2%) and in group B it was found cure 22(68.8%), improvement 7(21.87%) and failure 3(9.4%) at one month. At two months in the group A clinical responder was found to cure 22(68.8%), improvement 5(15.6%), failure in 3(9.4%) and relapse 2(6.2%). In group B it was found cure 18(56.2%), improvement 6(18.75%), failure 4(12.5%) and relapse 4(12.5%). Both oral ketoconazole dose 200mg daily for 7 days versus single dose 400 mg of itraconazole can be effective in the treatment of tinea versicolor with extensive involvement.CBMJ 2020 July: Vol. 09 No. 02 P: 26-33